Case Study of Using Peer Instruction at Upper Secondary School - Šestáková, Jana (Scientia in educatione, 2016)
The article describes the results of the case study “Implementation of the Peer Instruction method into education in the Czech Republic”, trying to answer one main question: “How is the Peer Instruction method implemented into physics teaching at upper secondary Czech school?”. The data was collected through interviews with the teacher, lesson observation and questionnaires for the teacher and students. The teacher involved in the study had been interested in the method since 2009. The research ﬁndings resulting from lesson observation and students’ opinions are from the 2014/2015 school year, when the method was implemented with students aged 17–18 years in three physics classes taught at an upper secondary school, with the respective numbers of students being 28, 16 and 13. The research generated the following conclusions, among other things: (1) the method should ideally be used immediately after a presentation of a new topic, therefore e.g. once a month, (2) a maximum of two ConcepTest questions should be used within one 45-minute lesson, and (3) students’ responses should be collected by means of ï¬ashcards rather than by an electronic voting system. The teacher starting with the method expected that ConcepTest questions would be simple for students and the work pace would be faster. She tried to hasten the work and therefore sometimes did not give students enough time to think about their responses, occasionally even failing to provide the option of a second answer. Nevertheless, the participating students gave positive feedback on this method, strongly indicating that that they had learned more while using this method. They admitted that using ï¬ashcards during the ﬁrst answering was a strong incentive that boosted their motivation towards thinking about the answers. This article is intended for people interested in the Peer Instruction method, teachers and researchers in active learning.